The Study on Utilization of Grasshoppers Gelatine as Edible Film in Optimizing Environmentally Friendly Packaging - Siwi Qoirinisa; Astri Arnamalia; Mutiara Eka Permata; Risma Nurohmah Ramdani (Journal of Food and Pharmaceutical Sciences, 2022)
The use of plastic packaging as food wrappers cannot be separated from everyday life. This will certainly cause many environmental problems because of the nature of plastics that are difficult to degrade naturally. One alternative to overcome the use of plastic in food products is edible film. The edible film is a thin layer that is used as a coating for food that can be consumed and is environmentally friendly. The edible film can be made from gelatin as raw material. Gelatin has properties that can form gels, foam emulsifiers, and can maintain the elasticity of a material. In the food industry, gelatin is widely used as a stabilizer, adhesive, binder, gelling agent, thickener, foamer, and viscosity enhancer. In Indonesia, the need for gelatin is met by importing from gelatin-producing countries, so the price becomes very expensive. According to international trade statistics, in 2016 Indonesia imported 54 tons of gelatin from America. Nearly 90% of American gelatin is derived from pork. This raises public concerns about the safety and halalness of their products. Grasshoppers have a fairly high protein content, which is about 24%. The method used in this study is the manufacture of edible films using grasshopper gelatin extracted by the acid method using HCl with varying concentrations of HCl levels of 2, 4, and 6% and soaking time of 1, 2, 3, and 4 hours. The potential of grasshoppers to be used as gelatin is considered suitable with Indonesia's natural resources in the manufacture of edible films as an effort to optimize environmentally friendly packaging.